ICT and Society 11th IFIP TC 9 International Conference on Human Choice and Computers, HCC11 2014, Turku, Finland, July 30 - August 1, 2014, Proceedings - Kimppa, Kai; Whitehouse, Diane; Kuusela, Tiina; Phahlamohlaka, Jackie (IFIP Advances in Information and Communication Technology,, 2014)
This book constitutes the refereed proceedings of the 11th IFIP TC 9 International Conference on Human Choice and Computers, HCC11 2014, held in Turku, Finland, in July/August 2014. The 29 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are based on both academic research and the professional experience of information technologists working in the field. They have been organized in the following topical sections: society, social responsibility, ethics and ICT; the history of computing and its meaning for the future; peace, war, cyber-security and ICT; and health, care, well-being and ICT.